2004
DOI: 10.1056/nejmoa040127
|View full text |Cite
|
Sign up to set email alerts
|

Protected Carotid-Artery Stenting versus Endarterectomy in High-Risk Patients

Abstract: Among patients with severe carotid-artery stenosis and coexisting conditions, carotid stenting with the use of an emboli-protection device is not inferior to carotid endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
668
4
16

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,573 publications
(696 citation statements)
references
References 32 publications
8
668
4
16
Order By: Relevance
“…Several randomized studies and registries have shown similar outcomes when compared with carotid endarterectomy in high-risk populations (17,18). Emboli are known to be associated with a high neurological complication rate and are also recognized as a potential cause of periprocedural stroke during CAS.…”
Section: Discussionmentioning
confidence: 92%
“…Several randomized studies and registries have shown similar outcomes when compared with carotid endarterectomy in high-risk populations (17,18). Emboli are known to be associated with a high neurological complication rate and are also recognized as a potential cause of periprocedural stroke during CAS.…”
Section: Discussionmentioning
confidence: 92%
“…After removing duplicates, we screened the titles and abstracts of 1126 publications. A total of 48 publications underwent full-text review, of which 10 reports [13][14][15][29][30][31][32][33][34][35] of 4 RCTs reported relevant outcomes among asymptomatic patients. In addition, the corresponding author of 1 RCT 36 provided information on asymptomatic patients on request, yielding a total of 11 reports of 5 RCTs in our review.…”
Section: Search Resultsmentioning
confidence: 99%
“…In 3 RCTs, interventionists were required to have a minimum level of experience to participate in the study. [13][14][15][29][30][31][32][33][34][35] The median duration of follow-up ranged from 30 days to 10 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…SAPPHIRE (Stenting and Angioplasty With Protection in Patients at High Risk for Endarterectomy Investigators) included asymptomatic patients with >80% stenosis and found that CAS was associated with a lower risk of the composite outcome of stroke, MI, or death at 1 year than CEA (9.9% versus 21.5%). 22 These generalizabilities of the results are limited by the lack of a medical control arm and the high complication rates in both treatment arms that may exceed risk associated with medical therapy alone. Randomized trials of CAS compared with CEA have been performed, but the studies included both symptomatic and asymptomatic patients and did not include a control arm receiving medical therapy alone.…”
Section: Primary Stroke Prevention In Asymptomatic Carotid Stenosismentioning
confidence: 99%